Relationship between the type and quantity of dietary carbohydrates, and the lipid profile and ApoB100 in adults. (Universitas Scientiarum, 2010)
Objective. To establish if there is any relationship between the type and amount of dietary carbohydrates commonly consumed and the plasmatic levels of lipids, lipoproteins and apolipoprotein B100 (ApoB100). Materials and methods. The final sample was conformed by the database of 144 lecturers of the Pontificia Universidad Javeriana who had previously participated in another survey and from which we used information on their food habits, plasmatic lipid levels, lipoproteins and ApoB100.  To determine the relationship between the dependent and independent variables, simple and multiple correlation analyses were done. In the cases of no correlation we applied the independence Chi2 test to find the relationship with the consumption of total carbohydrates, sugars and total fiber. Additionally, with a one-factor analysis of variance we compared plasmatic levels of lipids, lipoproteins and ApoB100 with the consumption of total carbohydrates, sugars and fiber. Results. Most of the population consumes above the daily total carbohydrate recommendation, men presented greater carbohydrate consumption of the type of sugars and more elevated plasmatic levels of triglycerides and lipoproteins of very low density (VLDL), whereas women presented higher levels of their high density lipoproteins (HDL). When relating grams of each type of carbohydrates with the levels of lipids, lipoproteins and ApoB100, no significant correlation was found for any of the cases (p>0,05). Conclusion. There was no significant relationship between the type and amount of carbohydrates consumed with the plasmatic levels of lipids, lipoproteins and Apo B100. Key words: apolipoprotein B100, carbohydrates, plasmatic lipids, lipoproteins.